The Relationship between Negative Stem and Taxonomy of Multiple-Choice Questions in Residency Pre-Board and Board Exams - Mohammad Hasan Karegar Maher; Mohammad Barzegar; Masoumeh Gasempour (Tabriz University of Medical Sciences, 2016)
Introduction: Multiple-choice question tests are considered as one of the most common assessment methods, frequently used in university tests. This study examined the relationship between question taxonomy and negative stem questions in university pre-board tests in Tabriz University of Medical Sciences and national boards tests in internal medicine, general surgery, pediatrics and obstetrics and gynecology residency examination from 2010-2011. Methods: In this cross-sectional study, 2400 written multiple-choice questions related to the mentioned fields were studied in terms of the relationship between taxonomy levels of the questions and their stems. If there were a negative word or negative concept in the question body, it was considered a negative stem. Taxonomy was graded: taxonomy I, ability to remember facts, Taxonomy II, ability to interpret data and taxonomy III ability to solve a new problem. The data collected were analyzed by SPSS18. P-value<0.05 was considered significant. Results: A total of 2400 questions from 8 tests (board, pre-board) in 4 fields were studied. In total, 23.1% of pre-board tests and 16.6% of national board tests had negative stems and the difference was statistically significant (P=0.0001). In this study 31.1% of questions were designed with positive stems and 63.9% with negative stems in taxonomy level I(P=0.0001). There is a correlation between negative stem questions and their taxonomy. This means that 63.9% of negative stem and 31.1% of positive stem questions have been designed in taxonomy level I(P=0.0001). Conclusion: The use of negative stem questions considerably resulted in the design of low-level cognitive questions.